Educational utility of advanced three‐dimensional virtual imaging in evaluating the anatomical configuration of the frontal recess. Issue 2 (18th October 2016) - Agbetoba, Abib; Luong, Amber; Siow, Jin Keat; Senior, Brent; Callejas, Claudio; Szczygielski, Kornel; Citardi, Martin J.
Abstract : Background: Endoscopic sinus surgery represents a cornerstone in the professional development of otorhinolaryngology trainees. Mastery of these surgical skills requires an understanding of paranasal sinus and skull‐base anatomy. The frontal sinus is associated with a wide range of variation and complex anatomical configuration, and thus represents an important challenge for all trainees performing endoscopic sinus surgery. Methods: Forty‐five otorhinolaryngology trainees and 20 medical school students from 5 academic institutions were enrolled and randomized into 1 of 2 groups. Each subject underwent learning of frontal recess anatomy with both traditional 2‐dimensional (2D) learning methods using a standard Digital Imaging and Communications in Medicine (DICOM) viewing software (RadiAnt Dicom Viewer Version 1.9.16) and 3‐dimensional (3D) learning utilizing a novel preoperative virtual planning software (Scopis Building Blocks), with one half learning with the 2D method first and the other half learning with the 3D method first. Four questionnaires that included a total of 20 items were scored for subjects' self‐assessment on knowledge of frontal recess and frontal sinus drainage pathway anatomy following each learned modality. A 2‐sample Wilcoxon rank‐sum test was used in the statistical analysis comparing the 2 groups. Results: Most trainees (89%) believed that the virtual 3D planning software significantly improved their understanding of the spatial orientation of the frontal sinus drainage pathway. Conclusion: Incorporation of virtual 3D planning surgical software may help augment trainees' understanding and spatial orientation of the frontal recess and sinus anatomy. The potential increase in trainee proficiency and comprehension theoretically may translate to improved surgical skill and patient outcomes and in reduced surgical time.